Case report on an outbreak of theileriosis in a dairy herd: Could it be a co-infection of a virulent strain of Theileria mutans with Theileria parva? - Tarusikirwa, Dey Freeman; Ndhlovu, Daud Nyosi; Hove, Thokozani (International Journal of Veterinary Sciences Research, 2023)
This case report aimed to alert veterinarians of the possibility of simultaneous infections with more than one Theileria species in cattle herds in Zimbabwe. Cows (N=7) and a postmortem specimen from a dairy farm located in Chivhu, Mashonaland East province, Zimbabwe were presented for clinical and postmortem examination, respectively. On history taking, the herd had a decrease in milk yield and high cow mortalities. The presented live animals had a heavy tick burden and were febrile and lethargic. Post-mortem findings revealed strong evidence suggestive of theileriosis. Theileria schizonts and piroplasms were identified in stained lymph node aspirate, impression, and blood smears. The herd was managed using tetracyclines and buparvaquone together with an intensive dipping protocol until deaths had stopped. Both the clinical and postmortem findings were strongly suggestive of the possibility of a simultaneous infection with more than one Theileria species in this herd. Thus, these finding highlight the need to characterise the Theileria species profile in Zimbabwe.